Favouring Factors and Germs Involved in Infection of Open Leg Bone Fractures at Bonzola Hospital in Mbujimayi: Descriptive Cross-Sectional Study - Mukendi, Crispin Muamba; Shamuana, Roger Kamwema; Tshikomba, Hervé Mbuyamba; Tshilunda, Joseph Ngandu; Akinja, Sévérin Uwonda; Kandanda, Anaclet Tshinyangu; Kabamba, André Mutombo; Wakunga , Warach Gabriel (International Journal of Health, Medicine and Nursing Practice, 2025)
Purpose : Leg bone fractures are the most common skeletal fractures of the pelvic limb. The aim of this study was to determine the factors favoring infection of open leg bone fractures, and the germs involved. Methods: This descriptive cross-sectional study was carried out at Bonzola Hospital in Mbujimayi, D.R. Congo, from January 1, 2018 to June 30, 2021, and included patients with open leg bone fractures. The association between a factor and the occurrence of infection was assessed using the correlation test (considered significant if p ≤ 0.05). Results: Fracture site infection was found in 60.3% of open fractures, dominated by Staphylococcus aureus. Factors significantly associated with the occurrence of this infection were time from trauma to first aid, treatment received prior to hospital admission, type of treatment received prior to hospital admission (in a health center), prolonged time from trauma to hospital arrival, context of admission to Bonzola Hospital (emergency), Gustilo fracture type (II and III) and first bone treatment. Unique Contribution to Theory, Practice and Policy: Open leg bone fractures are common. Infection occurs particularly in Gustilo and Anderson types 2 and 3. There are controllable factors associated with the occurrence of infection.